Elucidations on judgment and concerted action on Hannah Arendt from Duns Scotus - Yangali Núñez, Oscar Edmundo (2024)
The present work traces the links between the concepts of judgment and concerted action in Hannah Arendt and what the author analyzes about the will in Duns Scotus. In these links it is demonstrated that it is in the postulates of Doctor Sutil where we find a remote foundation for these concepts. First, the primacy of the Scotist singular over the Thomist universal is exposed, manifesting the importance of thinking beyond established needs. Second, we discuss the active role of a free will as a preamble to concerted action and identifying the judgment in accordance with it. Finally, we reflect on what was covered in Scotus and Arendt about an action correctly understood and as part of a political community.